Determination of Total Glutathione in Dried Blood Spot Samples Using a High-Performance Liquid Chromatography - Kanďár, Roman; Štramová, Xenie; Drábková, Petra; Brandtnerová, Martina (Journal of chromatographic science, 2015)
A method is described for the determination of total glutathione (TGSH) in dried blood spot (DBS) samples using high-performance liquid chromatography with fluorescence detection. Whole blood and DBS samples were obtained from a group of blood donors. After GSH reduction with dithiothreitol and protein precipitation with ethanol, the samples were derivatized with naphthalene-2,3-dicarboxaldehyde to form a very stable, highly fluorescent derivative. For the separation, a reversed phase HPLC method was used. The mixture of ethanol and deionized water (8 : 92, v/v) was used as a mobile phase. The analytical performance of this method was satisfactory: the intra- and interassay coefficients of variation were below 10%. Quantitative recoveries from spiked DBS samples were between 98.3 and 103.6%. The presented method is inexpensive and suitable for clinical testing purposes.
Keywords: Young Adult; methanol; Male; mladý dospělý; Adolescent; vysokoúčinná kapalinová chromatografie; test suché kapky krve; Adult; dospělí; mužské pohlaví; lineární modely; reprodukovatelnost výsledků; Methanol; Reproducibility of Results; Chromatography, High Pressure Liquid; mladiství; limita detekce; glutathion; lidé; ženské pohlaví; Dried Blood Spot Testing; Humans; Linear Models; Limit of Detection; Glutathione; Female; lidé středního věku; Middle Aged